The effects of fatigue on race walking technique - Hanley, B.; Drake, A. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
The purpose of this study was to measure the effects of fatigue on gait parameters during race walking. Research has shown that fatigued athletes require gait alterations in order to maintain speed. Eighteen competitive race walkers walked either 5 km or 10 km at a pace equivalent to 105% of their season`s best time. Junior athletes walked 5 km, while senior athletes (mostly 20 km walkers) walked 10 km. Kinetic data were collected using a Gaitway treadmill (1000 Hz). Data were collected at three points during the 5 km walks and at four points during the 10 km walks. Repeated measures ANOVA showed that there were significant differences in impulse and contact time parameters (p < .01). The kinetic and temporal changes occurred as early as 1 km. Athletes are recommended to race at a constant pace to reduce the effects of fatigue.